Application of the Abaqus *Fabric Model to Approximate the Draping Behavior of UD Prepregs Based on Suited Mechanical Characterization - Osterberger, Joachim; Maier, Franz; Hinterhölzl, Roland M. (Frontiers in Materials, 2022)
The increasing demand for automated manufacturing processes for carbon fiber reinforced polymers necessitates accurate forming simulations. For that purpose, the multi-purpose FE solver Abaqus provides the phenomenological *Fabric material model. While it is designed for woven materials, both structural directions and shear properties can be independently adjusted. We aim to quantify its applicability to model forming of a UD semifinished prepregs in a diaphragm forming station. We describe the material characterization and modelling and validate the results using accurate laser scans of manufactured parts. Various simulation aspects are methodically altered to better gauge their impact on the simulated forming result. The largest impact has an accurate depiction of the bending behavior, which is governed by the material behavior under compression in the *Fabric material model. But other aspects, like rate dependent modelling of the transverse direction and anisotropic properties for friction should be considered. Overall, a good agreement with experimental results, including regions with fiber bridging or the formation of folds and the contour of the part could be achieved.